Fate of Escherichia coli artificially inoculated in Tenebrio molitor L. larvae rearing chain for human consumption. (July 2022) - Cesaro, Cristiana; Mannozzi, Cinzia; Lepre, Adolfo; Ferrocino, Ilario; Corsi, Lorenzo; Franciosa, Irene; Belleggia, Luca; Milanović, Vesna; Cardinali, Federica; Garofalo, Cristiana; Cocolin, Luca; Aquilanti, Lucia; et al.
Graphical abstract: Highlights: E. coli dynamics in a T. molitor rearing chain for food production were studied. The microbiota of T. molitor eggs was investigated. The results showed that E. coli was not able to grow in the insect larvae. No accumulation of viable E. coli cells in the insect frass was observed. The dominance of Lactococcus was observed in the insect larvae. Abstract: The edible insect food chain represents a relatively novel food-producing system; hence, associated biological risks still need to be exhaustively evaluated. In the present study, the dynamics of Escherichia coli during the whole living period of Tenebrio molitor larvae (from eggs to pupae) were studied. To this end, a rearing substrate consisting of organic wheat middlings was spiked with E. coli cells at two initial contamination levels: 1 log cfu g −1 (low) and 6 log cfu g −1 (high). Microbial viability counting coupled with metataxonomic analyses was used to assess i) the persistence and growth of E. coli in the rearing substrate (wheat middlings); ii) the colonization and growth of E. coli in the insect larvae; and iii) the occurrence and load of E. coli in the frass (excrement from larvae mixed with substrate residues). The results highlighted a very limited persistence of the pathogen in all analyzed samples. In more detail, the results suggested that when E. coli was present at very low levels in the eggs of the insect, the pathogen was not able to reach concerning levels in the larvae. Moreover, when E. coli was present in the wheat middlings used for rearing, the environmental conditions of the substrate (low aw values) were not favorable for its survival and multiplication, irrespective of the presence of the larvae and their frass. Surprisingly, under the conditions applied in the present study, the larvae fed wheat middlings contaminated with E. coli seemed to be inhospitable or even hostile environments for microbial survival or multiplication. To explain the low levels of E. coli cells in the larvae reared in the present study, many factors can be considered, including the immune response of the host, microbial composition and interactions established in the gut of larvae, and insect species. Of note, part of the major fraction of the microbiota of larvae at the end of rearing was represented by Lactococcus, thus suggesting a possible effect of this lactic acid bacterium on E. coli decay. Further research is needed to better clarify the interactions between E. coli and the insect gut, as well as the interactions established among the target microorganism and those naturally harbored by the insect gut.